Polemic of Involvement of Notaries As Suspects Based On Article 263 of The Criminal Law Book - Devi Andiya Fidiyanti; Khunsul Yaqin (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
Purpose of this study is to analyze the criminal liability given to a Notary when he is also a suspect for his duties and authority to make an authentic deed. Second, to analyze the definition of the Notary Position and its duties and authorities. This research uses normative legal research methods. This study concludes: The criminal liability given to a Notary when he is also a suspect and is burdened with Article 263 of the Criminal Code for his duties and authorities to make an authentic deed is very detrimental to the Notary concerned, thus the Notary must have integrity, be smart and adhere to the code ethics and regulations for the position of a notary in carrying out his position. The making of a Notary deed still pays attention to every important point, which is allowed by the laws and regulations, and which is prohibited. Notaries are public officials who have the task and authority to make authentic deeds, in which there is the will of the parties. Then the position of a Notary and its duties and authorities are very much needed for the people of Indonesia, so what has been given by this law must be carried out as well as possible. good by the Notary, so as not to make the Notary a suspect for the authentic deed he made. In this case, the notary is also responsible for fulfilling the responsibilities of the will of the parties stated in the deed he made, so that the notary must be smart and have integrity so that there will be no disputes in the future.